HUBUNGAN PEMBERIAN REWARD TERHADAP HASIL BELAJAR BAHASA INDONSEIA SISWA KELAS TINGGI SD INPRES 12/79 PANYIWI KECAMATAN CENRANA KABUPATEN BONE - Satriani DH; Abd.Hafid; Nusrah Mustamirrah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a quantitative research with correlational type that aims to determine the relationship between reward giving and Indonesian language learning outcomes of high grade students of SD Inpres 12/79 Panyiwi, Cenrana District, Bone Regency. The population in this study were all students of grades IV, V and VI of SD Inpres 12/79 Panyiwi, with a sample of 36 students selected using saturated sampling techniques. The research data were obtained through questionnaires and documentation. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. Based on the results of the descriptive statistical analysis, the reward giving was in the very good category with a percentage of 86.05%, while the Indonesian language learning outcomes also showed similar results which were in the very good category with a percentage of 83.85%. The results of the inferential statistical analysis showed that there was a significant relationship between reward giving and students' Indonesian language learning outcomes with a correlation coefficient of 0.619 which was included in the strong category, so it can be concluded that there is a positive and significant relationship between reward giving and Indonesian language learning outcomes of high grade students of SD Inpres 12/79 Panyiwi, Cenrana District, Bone Regency.